Answer:
A. 4x²+20x+25
Step-by-step explanation:
Because of PEMDAS, you calculate the value inside of the parenthesis first, so you expand [2x+1-(4x+6)]:
2x+1-4x-6 = -2x-5.
Then apply the exponent:
(-2x-5)² = (-2x-5)(-2x-5) = 4x²+10x+10x+25 = 4x²+20x+25
Answer:
4:1
Step-by-step explanation:
Total = Principal * e^(rate*years)
Total = 4,500 * 2.718281828459^(.02*4)
Total = 4,500 * 2.718281828459^(.08)
Total = 4,500 *
<span>
<span>
</span></span>
<span>
<span>
<span>
1.0832870677
</span>
</span>
</span>
Total =
<span>
<span>
<span>
4,874.79
</span>
</span>
</span>
calculator for checking the answer:
http://www.1728.org/compint.htm
4x + 7 <=== ur expression
Answer: $1500 + 3% + $82,975= 84475.03
Step-by-step explanation: